2011
DOI: 10.1007/s10354-010-0856-4
|View full text |Cite
|
Sign up to set email alerts
|

Coverage of recommended vaccinations in subjects with diabetes mellitus and ischemic heart disease: results for women and men

Abstract: Vaccination is an important public health strategy to prevent adverse health outcomes in the general population and in subjects with chronic diseases. It was the aim of this study to compare data on coverage of recommended vaccinations in men and women with diabetes mellitus and after myocardial infarction (MI) and to analyse trends in three different interview surveys: 1991, 1999 and 2006-07. The data show a rise in influenza vaccination coverage rate in men and women in the general population and in high-ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…In general, females have a tendency to prefer healthy lifestyle. Thus, they have higher probability to get health information and take preventive action like vaccination than males [36,37]. However, other previous studies have shown higher vaccination rates in males [38,39].…”
Section: Discussionmentioning
confidence: 91%
“…In general, females have a tendency to prefer healthy lifestyle. Thus, they have higher probability to get health information and take preventive action like vaccination than males [36,37]. However, other previous studies have shown higher vaccination rates in males [38,39].…”
Section: Discussionmentioning
confidence: 91%
“…A basic genomic view reveals that while the Y chromosome carries mainly genes associated with sexual function, the X chromosomes harbor genes coding for physiological processes of the heart, brain and immune system. As a result, women, carrying two copies of the X chromosome, although one of them is silenced, have a stronger immune system than men, a lower risk for infectious disease and better antibody production following vaccination [ 5 , 6 ]. On the other hand, women are also more frequently affected by autoimmune disease like multiple sclerosis and rheumatic disease [ 5 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…In 2004, most topics were related to cardiovascular disease, public health, and osteoporosis, whereas in 2006 the main topic was gender-differences In this journal we have covered a broad spectrum of medical areas with a focus on endocrinology and metabolism [7], including reproductive health, but also referring to the important topic of kidney transplantation [8] and heart failure [9], and to prevention and public health [10,11] as well as medical education [12] from a gender perspective. There are many unsolved important questions regarding sex-and gender differences.…”
mentioning
confidence: 98%